2019
DOI: 10.1021/acs.nanolett.9b02581
|View full text |Cite
|
Sign up to set email alerts
|

Massive Vacancy Concentration Yields Strong Room-Temperature Ferromagnetism in Two-Dimensional ZnO

Abstract: Two-dimensional (2D) ZnO nanosheets with highly concentrated Zn vacancies (V Zn ) of up to approximately 33% were synthesized by ionic layer epitaxy at the water−toluene interface. This high cation vacancy concentration is unprecedented for ZnO and may provide unique opportunities to realize exotic properties not attainable in the conventional bulk form. After annealing, the nanosheets showed characteristic magnetic hysteresis with saturation magnetization of 57.2 emu/g at 5 K and 50.9 emu/g at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…[ 10 ] For instance, ZnO nanosheets with highly concentrated Zn vacancies ( V Zn ) exhibit higher magnetism than other ZnO nanostructures and comparable to the conventional ferrimagnetic Fe 3 O 4 . [ 11 ] Interestingly, Wang et al reported a p‐type nonstoichiometric Ni 1− x O involving a semiconductor‐to‐insulator‐to‐metal transition with the formation of oxygen (anionic) vacancy defects, which provides a new understanding to defect effect. [ 12 ] Inspired by the results, it is of pivotal importance to harmonize the electronic structures combining the facet engineering and defect engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ] For instance, ZnO nanosheets with highly concentrated Zn vacancies ( V Zn ) exhibit higher magnetism than other ZnO nanostructures and comparable to the conventional ferrimagnetic Fe 3 O 4 . [ 11 ] Interestingly, Wang et al reported a p‐type nonstoichiometric Ni 1− x O involving a semiconductor‐to‐insulator‐to‐metal transition with the formation of oxygen (anionic) vacancy defects, which provides a new understanding to defect effect. [ 12 ] Inspired by the results, it is of pivotal importance to harmonize the electronic structures combining the facet engineering and defect engineering.…”
Section: Introductionmentioning
confidence: 99%
“…[10] For instance, ZnO nanosheets with highly concentrated Zn vacancies (V Zn ) exhibit higher magnetism than other ZnO nanostructures and comparable to the conventional ferrimagnetic Fe 3 O 4 . [11] Interestingly, Wang et al reported a p-type nonstoichiometric Ni 1−x O involving a semiconductor-to-insulator-to-metal transition with the formation of oxygen (anionic) vacancy defects, which…”
mentioning
confidence: 99%
“…ZnO HNWA has the highest M s is ~7.1 emu/g. Two-dimensional (2D) nanosheets/nanoplates have been synthesized by HYT [45,82,83] and ionic layer epitaxy (ILE) [41] in Figure 9. The average thickness of ZnO Nanoplates is estimated to be ~20 nm by the SEM images and XRD peak.…”
Section: Other Nanostructuresmentioning
confidence: 99%
“…Two-dimensional ZnO nanosheets with high V Zn concentration have been grown by ILE [41] (Figure 9E,G). The nanosheets annealed in Ar at 400 • C for 1h show M s of 50.9 emu/g in Figure 9G.…”
Section: Other Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation